Dampak Integrasi Problem Based Learning dengan Google Earth- Degradasi Lingkungan terhadap Keterampilan Berpikir Kritis Siswa SD: The Impact of Integrating Problem Based Learning with Google Earth-Environmental Degradation on Elementary School Students' Critical Thinking Skills - Nirwati Nirwati; Mulyono Mulyono; Darnanengsi Darnanengsi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aimed to analyze the impact of integrating problem-based learning (PBL) with Google Earth on the critical thinking skills of elementary school students. This study employed a quantitative approach with a quasi-experimental design, employing a pretest-posttest experimental-control group design. Fifty elementary school students were selected through purposive sampling, consisting of 26 students in the experimental group and 24 students in the control group. The research instruments included a critical thinking skills test based on Facione's dimensions (interpretation, analysis, evaluation, inference, and explanation), as well as an observation sheet to measure learning activities. The results of the ANCOVA analysis of the pretest-posttest scores showed a significant increase in students' critical thinking skills in the experimental group (p < 0.001, Cohen's d = 3.24), indicating a very strong effect.Furthermore, the MANOVA and ANOVA results also confirmed a significant increase in all five dimensions of critical thinking, with the largest effect being on the evaluation dimension. These findings suggest that integrating satellite imagery into PBL learning can provide a contextual and meaningful learning experience. Thus, the use of technology like Google Earth not only enhances critical thinking skills but also fosters deeper environmental awareness in students. It is hoped that this learning implementation can become an innovative alternative in environmental education in elementary schools.